Youth activity spaces and daily exposure to tobacco outlets. (July 2015) - Lipperman-Kreda, Sharon; Morrison, Christopher; Grube, Joel W.; Gaidus, Andrew
Abstract: We explored whether exposure to tobacco outlets in youths׳ broader activity spaces differs from that obtained using traditional geographic measures of exposure to tobacco outlet within buffers around homes and schools. Youths completed an initial survey, daily text-prompted surveys, and carried GPS-enabled phones for one week. GPS locations were geocoded and activity spaces were constructed by joining sequential points. We calculated the number of tobacco outlets around these polylines and around homes and schools. Results suggest that activity spaces provide a more accurate measure of tobacco outlet exposures than traditional measures. Assessing tobacco outlet exposure within activity spaces may yield significant information to advance the field. Highlights: Measures of tobacco outlets around homes and schools misrepresent youth exposure. Activity spaces may provide a better measure of tobacco outlet exposure.